Skrining Pre Eklampsia - I Komang Lindayani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2018)
Maternal Mortality Rate (MMR) or Angka Kematian Ibu (AKI) in Indonesia is still high. One of the causes of AKI is pre-eclampsia (PE). Screening in the first trimester is effective in determining prevention of PE. This study aims to examine the results of research on pre-eclampsia screening. The study found that a complete history of maternal health characteristics and history combined with biophysical and biochemical examinations was significantly able to predict the likelihood that a pregnant woman could develop pre-eclampsia. Midwives can conduct screening efforts through an adequate history related to the characteristics and health history of pregnant women and through blood pressure testing to obtain an accurate Mean Arterial Pressere / MAP.